2016
DOI: 10.1136/acupmed-2015-010951
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Relieves Labour Pain and Influences the Spinal Dynorphin/κ-Opioid Receptor System in Rats

Abstract: The present study indicates that EA relieves labour pain, at least in part, by regulation of the spinal DYN/KOR system in a rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…The Animal Experimental Centre of Guangxi Medical University (Nanning, China) provided Sprague-Dawley rats, aged 3 months and weighing 250–350 g. After 7 days of environmental adaption, the female rats were maintained with male rats (1:1 ratio) to induce copulation indicated by a sperm-positive vaginal smear, and then given castor oil to trigger labour as previously described. 9 The rats in labour were randomly assigned to three groups according to the different treatments: the control group (n=30), which did not received any treatment; the remifentanil group (n=30), which received remifentanil at a dose of 5 µg/kg/min (Yichang Humanwell Pharmaceutical Co, Ltd, Yichang, China) by injection into the caudal vein; and the EA group (n=60), which was randomly divided into two subgroups: the Jiaji group (n=30) and the SP6+LI4 group (n=30). The rats in the Jiaji group were given EA at bilateral Jiaji , and the rats in the SP6+LI4 group received EA at SP6 ( Sanyinjiao ) and LI4 ( Hegu ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Animal Experimental Centre of Guangxi Medical University (Nanning, China) provided Sprague-Dawley rats, aged 3 months and weighing 250–350 g. After 7 days of environmental adaption, the female rats were maintained with male rats (1:1 ratio) to induce copulation indicated by a sperm-positive vaginal smear, and then given castor oil to trigger labour as previously described. 9 The rats in labour were randomly assigned to three groups according to the different treatments: the control group (n=30), which did not received any treatment; the remifentanil group (n=30), which received remifentanil at a dose of 5 µg/kg/min (Yichang Humanwell Pharmaceutical Co, Ltd, Yichang, China) by injection into the caudal vein; and the EA group (n=60), which was randomly divided into two subgroups: the Jiaji group (n=30) and the SP6+LI4 group (n=30). The rats in the Jiaji group were given EA at bilateral Jiaji , and the rats in the SP6+LI4 group received EA at SP6 ( Sanyinjiao ) and LI4 ( Hegu ).…”
Section: Methodsmentioning
confidence: 99%
“…Before and after treatment, the labour pain of the rats in each group was assessed by the warm water tail-flick test as previously described. 9 In brief, the distal part of the rats’ tails (4 cm length) were dipped into water at a temperature of 50±0.5°C. The time interval after which the tail withdrew from the water was recorded and taken as a measure of pain threshold.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu J [6] found electroacupuncture Relieves Nerve Injury-Induced Pain Hypersensitivity via the Inhibition of Spinal P2X7 Receptor-Positive Microglia. Jiang QY [7] found that electroacupuncture relieves labour pain and influences the spinal dynorphin/kappa-opioid receptor system in rats.…”
Section: Spinal Cord Level Integrationmentioning
confidence: 99%
“…2022 Acupuncture can also be used to control body weight and attenuate stroke-induced learning and memory deficits. 23,24 Recently, many studies have demonstrated that the anti-nociceptive properties of acupuncture are mediated by the release of endogenous opiates 2527 and adenosine28, 29 and may also be related to changes in the expression of various proteins, including the NMDARs, ASIC3, TRPV1, TRPV4 and Nav channels. 3033 Recent studies have demonstrated that TRPV1 or pERK is increased in the peripheral dorsal root ganglion (DRG), central amygdala and thalamus in the acid saline injection-induced mouse FM model.…”
Section: Introductionmentioning
confidence: 99%